The Influence of Organizational Culture, Physical Work Environment, and Work Life Balance on Job Satisfaction of Employees of the Investment and One-Stop Integrated Services Department of Kediri City - Widyawan, Agit; Wardhani, Rike Kusuma; Munawaroh, Nuril Aulia (CV. Lenggogeni Data Publishing, 2023)
This research aims to explain the influence of Organizational Culture, Physical Work Environment and Work Life Balance on employee job satisfaction at the Kediri City Department (PMPTSP). The data analysis techniques used in this research are validity test, reliability test, classical assumption test, multiple linear regression test, t test, F test with SPSS version 24.0 tools. The methods used are questionnaires, interviews and observations. The sampling technique used purposive sampling technique with a total of 32 respondents. Based on the research results obtained from the multiple linear regression equation Y = 1.330 + 0.272X 1 + 0.201X2 + 0.400X3 + e. The results of the analysis carried out show that the Organizational Culture variable has a positive and significant effect on employee job satisfaction with evidence of Sig. 0.007 < 0.05 and the regression coefficient is positive 0.272. The Physical Work Environment variable has a positive and significant effect on employee job satisfaction with evidence of Sig. 0.046 < 0.05 and the regression coefficient is positive 0.201. The Work Life Balance variable has a positive and significant effect on employee job satisfaction with evidence of Sig. 0.005 < 0.05 and the regression coefficient is positive 0.400. And Organizational Culture, Physical Work Environment and Work Life Balance simultaneously have a significant influence on employee job satisfaction with evidence of Sig. 0.000 < 0.05 R Square value 0.651 or 65.1%.